2013
DOI: 10.1039/c2sm26621k
|View full text |Cite
|
Sign up to set email alerts
|

Fast and reversible microscale formation of columns in carbon nanotube suspensions

Abstract: Homogeneous carbon nanotube suspensions are studied in the semidilute regime, which is permitted by the use of an effective polysiloxane surfactant, PySi70, as a liquid matrix. We study such suspensions under an AC electric field by optical microscopy, transient light transmission and impedance spectroscopy. Optical microscopy shows the formation of long-range microscale columnar order as a result of a fast field-induced phase separation. The aggregation process is found to be reversible and repeatable, with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Polymeric composites based on carbon nanotubes (CNTs) and graphene nanosheets (GNSs), because of their outstanding physical and mechanical properties, have attracted increasing attention . It has been found that many physical behaviors of the polymer matrix, such as the glass transition, phase separation, and crystallization, are dramatically altered through the incorporation of carbon nanofillers, which eventually have a significant influence on the properties of the ultimate composites, that is, the mechanical properties, thermal conductivity, and electromagnetic shielding properties . In addition, the structural characteristics of CNTs and GNSs and their physical interactions originating from their high aspect ratios and high specific surface areas are closely related to the phase behaviors and properties of carbon nanofiller/polymer composites …”
Section: Introductionmentioning
confidence: 99%
“…Polymeric composites based on carbon nanotubes (CNTs) and graphene nanosheets (GNSs), because of their outstanding physical and mechanical properties, have attracted increasing attention . It has been found that many physical behaviors of the polymer matrix, such as the glass transition, phase separation, and crystallization, are dramatically altered through the incorporation of carbon nanofillers, which eventually have a significant influence on the properties of the ultimate composites, that is, the mechanical properties, thermal conductivity, and electromagnetic shielding properties . In addition, the structural characteristics of CNTs and GNSs and their physical interactions originating from their high aspect ratios and high specific surface areas are closely related to the phase behaviors and properties of carbon nanofiller/polymer composites …”
Section: Introductionmentioning
confidence: 99%